Oxytocin pathways and the evolution of human behavior - Carter, C Sue (Annual review of psychology, 2014)
This review examines the hypothesis that oxytocin pathways--which include the neuropeptide oxytocin, the related peptide vasopressin, and their receptors--are at the center of physiological and genetic systems that permitted the evolution of the human nervous system and allowed the expression of contemporary human sociality. Unique actions of oxytocin, including the facilitation of birth, lactation, maternal behavior, genetic regulation of the growth of the neocortex, and the maintenance of the blood supply to the cortex, may have been necessary for encephalization. Peptide-facilitated attachment also allows the extended periods of nurture necessary for the emergence of human intellectual development. In general, oxytocin acts to allow the high levels of social sensitivity and attunement necessary for human sociality and for rearing a human child. Under optimal conditions oxytocin may create an emotional sense of safety. Oxytocin dynamically moderates the autonomic nervous system, and effects of oxytocin on vagal pathways, as well as the antioxidant and anti-inflammatory effects of this peptide, help to explain the pervasive adaptive consequences of social behavior for emotional and physical health.